Impaired White Matter Connections of the Limbic System Networks Associated with Impaired Emotional Memory in Alzheimer's Disease - Li, Xiaoshu; Wang, Haibao; Tian, Yanghua; Zhou, Shanshan; Li, Xiaohu; Wang, Kai; Yu, Yongqiang (Frontiers in Aging Neuroscience, 2016)
Background: Discrepancies persist regarding retainment of emotional enhancement of memory (EEM) in mild cognitive impairment (MCI) and early Alzheimer’s disease (AD) patients. In addition, the neural mechanisms are still poorly understood, little is known about emotional memory related changes in white matter (WM). Objective: To observe whether EEM is absent in amnestic MCI (aMCI) and AD patients, and to investigate if emotional memory is associated with WM connections and gray matters (GM) of the limbic system networks. Methods: Twenty-one AD patients, 20 aMCI patients and 25 normal controls participated in emotional picture recognition tests and MRI scanning. Tract-based spatial statistics (TBSS) and voxel-based morphometry (VBM) methods were used to determine white and gray matter changes of patients. Fourteen regions of interest (ROI) of WM and 20 ROIs of GM were then selected for the correlation analyses with behavioral scores. Results: The EEM effect was lost in AD patients. Both white and gray matter of the limbic system networks were impaired in AD patients. Significant correlations or tendencies between the bilateral uncinate fasciculus, corpus callosum (genu and body), left cingulum bundle, left parahippocampal WM and the recognition sensitivity of emotional valence pictures, and significant correlations or tendencies between the splenium of corpus callosum, left cingulum bundle, left crus of fornix and stria terminalis and the recognition sensitivity of EEM were found. The volume of left amygdala, bilateral insula, medial frontal lobe, anterior and middle cingulum gyrus were positively correlated with the recognition sensitivity of emotional photos, and the right precuneus was positively correlated with the negative EEM effect. However, the affected brain areas of aMCI patients were more localized, and aMCI patients benefited only from positive stimuli. Conclusion: There are impairments of the limbic system networks of AD patients. Damaged WM connections and GM volumes of those networks are associated with impaired emotional memory and EEM effect in AD patients.